Synthesis and Characterization of Novel Plasmid-Layered Double Hydroxides Nanobiohybrids for Gene Delivery - Masarudin, Mas Jaffri (2008)
One of the hindering problems faced by conventional gene delivery systems into cells is their efficiency in its delivery and integration. DNA and other genetic materials are easily degraded in both the extracellular as well as intracellular matrix by both endonuclease activities and physiological conditions of the cellular environment. Therefore, research insights have focused on utilizing the emerging field of nanotechnology to overcome this problem. For this reason , a layered nanomaterial, Mg/AI-LD H based on the layered double hydroxide (LDH) system was synthesized at pH 1 0.0 at different Mg to AI ratios, to determine whether it can be used as a vector for gene delivery. A plasmid DNA, encodi ng the green fluorescent protein reporter gene, was intercalated into the LDH intergallery region; previously occupied by nitrate anions. Successful occupation of the circular DNA was confirmed by expansions within the intergallery spacing of the LDH from powder x-ray diffraction analysis. Fourier-transform infrared spectroscopy further revealed the presence of exclusive functional groups belonging to both DNA and LDH in the nanobiohybrid product, and by both CHNS as well as gel electrophoresis data, the plasmid DNA was confirmed to be successfully intercalated within the LDH host. The effects of the host on cells were then evaluated using MTT assay on two cell lines, and the synthesized LDH hosts were found to have no significant lethal effects on cell viability. Microscopic studies using S EM and TEM later revealed the nanobiohybrid size to be withi n the nano-meter range, which was found to enhance its uptake b y cells. Cells transfected with the nanobiohybrid showed successful expression of the GFP gene compared to controls, as observed using fluorescence microscopy. The nanobiohybrid was found to not only deliver the gene into cells, but gene expression efficiency using the host for transfection was even comparable to a commercially available, high cost transfection vector in the market. Compared to the commercial vector, the LDH host was also shown to provide sufficient protection of the intercalated plasmid from degradation by the DNase I and XhollKpnl restriction enzymes, showing the potential of using the LDH host as an alternative delivery vector for gene delivery.